Implementing Onshore Wind Power Projects - Elizondo Azuela, Gabriela; Ben, Rafael (World Bank, Washington, DC, 2014)
The kinetic energy in wind is converted into mechanical power in specialized propeller-driven turbines mounted on towers. A generator inside the turbine converts the mechanical power into electricity. Utility-scale wind turbines range in size from 100 kilowatts to as large as several megawatts. Turbines can be built on land or offshore and are grouped into 'wind farms' that provide bulk power to the electrical grid. Smaller turbines are used for homes, telecommunications dishes, and water pumping, sometimes in connection with diesel generators, batteries, and photovoltaic systems. Such hybrid wind systems are typically used in remote, off-grid locations, where a connection to the utility grid is not available. This note focuses on onshore wind energy, which is more widely established and has lower risks than offshore wind.